Experimental Examination of Component-Differentially-Challenged XOR PUF Circuits. Issue 1 (January 2021) - Mursi, Khalid T.; Zhuang, Yu
Abstract: Physical unclonable functions (PUFs), leveraging tiny physical variations of the circuits to produce unique responses for individual PUF instances, are emerging as a promising class of hardware security primitives for resource-constrained IoT devices. Component-differentially-challenged XOR PUFs (CDC XPUFs) are among the PUFs which were shown to be highly secure to machine learning modeling attacks. However, no study of implementation and experimentation has been carried out. In this paper, we report our implementations of CDC XPUFs on FPGAs and experimental studies of the essential properties of CDC XPUFs.